2021
DOI: 10.1108/jfp-12-2020-0055
|View full text |Cite
|
Sign up to set email alerts
|

Working in a prison: Challenges, rewards, and the impact on mental health and well-being

Abstract: Purpose Prisons are uniquely challenging working environments. Staff are often exposed to direct and indirect trauma, impacting negatively on their mental well-being. Due to the limited research into prison staff experience, this paper aims to explore what staff find most challenging, how they cope, what support they would like and rewarding aspects of their work. Design/methodology/approach This service development project was facilitated through a staff well-being event. A qualitative approach was used and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…One of the major limitations in interpreting our results is that we do not have pre‐lockdown or pre‐Covid‐19 baseline assessments to look at the trajectory of mental health outcomes in prison staff over time. It is known from the literature, that there are numerous other variables in correctional settings (such as prisoner self‐harm or suicide attempts) that can be directly or indirectly traumatising for staff (Dennard et al., 2021; Lerman, Harney & Sadin, 2021; Page & Robertson, 2021). Research has also shown that a positive organisational climate and good communication is associated with improved mental well‐being (Kyprianides et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major limitations in interpreting our results is that we do not have pre‐lockdown or pre‐Covid‐19 baseline assessments to look at the trajectory of mental health outcomes in prison staff over time. It is known from the literature, that there are numerous other variables in correctional settings (such as prisoner self‐harm or suicide attempts) that can be directly or indirectly traumatising for staff (Dennard et al., 2021; Lerman, Harney & Sadin, 2021; Page & Robertson, 2021). Research has also shown that a positive organisational climate and good communication is associated with improved mental well‐being (Kyprianides et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies included in this review highlighted interpersonal stressors, such as lack of social support from managers and co‐workers and lack of communication between management and staff as among the most stressful features of frontline correctional work. In addition, prison officers regularly experience direct and indirect trauma (Dennard et al., 2021). Persistent exposure to indirect trauma (such as prisoner self‐harm or suicide attempts) can have serious negative consequences on prison staff (Page & Robertson, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…If stabilization-a condition of balance among the members-is not reached, the team may experience disorganization-a general lack of balance and chaos. Such a condition could be a prerequisite for the development of syndromes such as burnout, which has been associated with working in a challenging prison environment [6].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the challenging nature of the task, in the prison environment, there is a limited or sporadic offering of potentially useful support systems such as regular supervision or reflective practice [6]. Prison workers reported needing a space to discuss their role and reflect on difficult situations with their colleagues [7].…”
Section: Introductionmentioning
confidence: 99%
“…The prison environment presents additional challenges and is known to have a detrimental effect on mental wellbeing [17][18][19][20][21], while funding cuts and over-crowding contribute to an increasingly negative experience [21,22]. Physical and mental health outcomes for staff who work in prisons are also poor due to the challenging work, unpleasant environment, and experience of direct and vicarious trauma, which may make staff a vulnerable population too [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%